Cashew Apple Juice Anacardium Occidentale L Probiotic Fermented from Lactobacillus acidophilus - Nguyen, Giang Thi Thuy; Nguyen, Kieu Thu; Tran, Nam Nhat; Dong, Dao Thi Anh; Nguyen, Minh Phuoc (European Journal of Sustainable Development, 2013)
The development of these probiotic beverages is important to diversify the market and toattend benefits to human health of large intestine. The aim of this study is using fruit juicefrom cashew apple as a substrate for the growth of Lactobacillus acidophilus. In order tocreate a new good probiotic beverages for human health and decrease environmentalimpurity from ripe cashew apples. The result shows that juice from ripe cashew applesafter remove tannin and pasteurization at 900C on 10 minutes and additional 11% (w/v)sucrose can be suitable substance for growthing of Lactobacillus acidophilus.The optimumconditions of Lactobacillus acidophilus growth in cashew apple juice are: the initial pH4.0-4.5, the temperature value 370C. Cell biomass of L. acidophilus after being fermentedat 370C/48 hours is greater109 cfu/mL.